STRUKTUR KOMUNITAS GASTROPODA DAN DISTRIBUSI SPASIAL MELANOIDES PLICARIA DI CIBINUA UJUNG KULON - D. I. HARTOTO; ISTIYANTI M. MARWOTO (BERITA BIOLOGI, 1986)
D.I. HARTOTO & RISTIYANTI M. MARWOTO.1986. Community structure and spatial distribution of Melanoides plicaria at Cibinua, Ujung Kulon. Berita Biologi 3(4): 155 - 158. The study was conducted during the dry and rainy seasons of the year 1983 and 1984, on upstream and downstream segment of Cibinua, Ujung Kulon National Park in order to reveal the pattern of distribution and corelation with its habitat structures.The gastropod community was dominated by M. plicaria and most the other species are found in only small number, which is in accordance with the published data of their genera distribution.Distribution of M.plicaria indicated a similar patchy pattern in all season and segment, but suspected due to different mechanisms.There is a clear individual packing phenomenon but do not distinctively shows an aggregation condition.Different corelation pattern between number of individuals per plot and weighted scores olphysical structure is found in all season and segment. Exclusive competition between the predo minant gastropod and the carnivorous and herbivorous fishes is briefly discussed.